Effect of insulin on ovarian response and embryo production in goats superovulated with eCG - Khan, M H; Agarwal, S K; Mazumdar, A C; Hoque, M; Shankar, U (The Indian Journal of Animal Sciences, 2005)
Effect of insulin on ovarian response and embryo production in goats. superovulated with eCG, was investigated. Sixteen nondescript, cyclic goats were divided randomly into 2 equal groups comprising of 8 animals in each group. The animals of group A (insulin treatment) were administered with long acting purified bovine insulin @ 0.2 IU/kg bw/goat/ day. subcutaneonsly on days 7, 8 and 9 of oestrous cycle and superovulated in next oestrous cycle using 750 IU eCG, on day 12 of the cycle. Animals of group B (control) were not received insulin but superovulated using same protocol. Animals responding to superovulation (8/8, 100% vs 618, 75%), ovulation rate (8.75±1.26 vs 7.75±2.38), unovulated large follicles ( 10.87±2.54 vs 5.35±1.14), total ovarian response (19.62±1.76 vs 13.12±1.68) and transferable embryo/ donor (1.87±0.37 vs 1.37±0.46) were higher in insulin pretreatment than control group indicating beneficial effect of insulin on superovulation.